2022
DOI: 10.1212/cpj.0000000000001181
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia Recurrence

Abstract: Background:Transient global amnesia (TGA) is an acute amnestic disorder with unclear pathophysiology. Although considered a benign phenomenon, the possibility of a recurrence is a major concern for the patient. Our objective is to identify the prevalence and risk factors of relapse, to help clinicians counsel patients about it.Methods:According to PRISMA guidance, we screened 1658 studies from MEDLINE, Lilacs and Embase databases, published from 1985 to April 2021, in English or Spanish. We included 36 observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“… Recent data show that the risk of TGA recurrence ranges from 12 to 27% [ 3 5 ]. Patients with TGA are significantly more likely (OR 2.5) to have a history of migraine [ 6 ].…”
Section: What’s New?mentioning
confidence: 99%
See 4 more Smart Citations
“… Recent data show that the risk of TGA recurrence ranges from 12 to 27% [ 3 5 ]. Patients with TGA are significantly more likely (OR 2.5) to have a history of migraine [ 6 ].…”
Section: What’s New?mentioning
confidence: 99%
“…A meta-analysis of 36 studies found a significant association between TGA recurrence risk and migraine, depression, and sexual activity as trigger factors [ 5 ].…”
Section: What’s New?mentioning
confidence: 99%
See 3 more Smart Citations